Influence of the implant diameter with different sizes of hexagon: Analysis by 3-dimensional finite element method - Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; De Moraes, Sandra Lúcia Dantas [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; De Carvalho, Paulo Sérgio Perri [UNESP]; Noritomi, Pedro Yoshito (American Academy of Implant Dentistry, 2013)
The aim of this study was to evaluate the stress distribution in implants of regular platforms and of wide diameter with different sizes of hexagon by the 3-dimensional finite element method. We used simulated 3-dimensional models with the aid of Solidworks 2006 and Rhinoceros 4.0 software for the design of the implant and abutment and the InVesalius software for the design of the bone. Each model represented a block of bone from the mandibular molar region with an implant 10 mm in length and different diameters. Model A was an implant 3.75 mm/regular hexagon, model B was an implant 5.00 mm/regular hexagon, and model C was an implant 5.00 mm/ expanded hexagon. A load of 200 N was applied in the axial, lateral, and oblique directions. At implant, applying the load (axial, lateral, and oblique), the 3 models presented stress concentration at the threads in the cervical and middle regions, and the stress was higher for model A. At the abutment, models A and B showed a similar stress distribution, concentrated at the cervical and middle third; model C showed the highest stresses. On the cortical bone, the stress was concentrated at the cervical region for the 3 models and was higher for model A. In the trabecular bone, the stresses were less intense and concentrated around the implant body, and were more intense for model A. Among the models of wide diameter (models B and C), model B (implant 5.00 mm/regular hexagon) was more favorable with regard to distribution of stresses. Model A (implant 3.75 mm/regular hexagon) showed the largest areas and the most intense stress, and model B (implant 5.00 mm/regular hexagon) showed a more favorable stress distribution. The highest stresses were observed in the application of lateral load.
Keywords: Biomechanics; Dental implants; Finite element analysis; compressive strength; dental procedure; finite element analysis; human; methodology; tensile strength; tooth implant; tooth prosthesis; Young modulus; Compressive Strength; Dental Implants; Dental Models; Dental Prosthesis Design; Dental Stress Analysis; Elastic Modulus; Finite Element Analysis; Humans; Tensile Strength